Real life experience of a screening strategy for latent tuberculosis before treatment with biologicals in indian patients with rheumatic diseases - Anand N Malaviya; Ravita Thakaran; Roopa Rawat; Sanjiv Kapoor; Shriram Garg; Sadhana S Baghel; Christy Messi; Vivekanand; Qamar Zaheer (Indian Journal of Rheumatology)
Objective: The objective of the study was to study the effectiveness of a recommended screening strategy for latent tuberculosis infection (LTBI) in patients with systemic inflammatory rheumatic diseases (SIRDs) treated with biological disease-modifying antirheumatic drugs (bDMARDs). Methods: The study included patients being considered for bDMARD treatment. Screening strategy included screening with “4S symptom complex (current cough, fever, weight loss, and night sweats) for TB,” augmented Mantoux test using ten tuberculin unit (TU) strength simultaneously with QuantiFERON®-TB Gold (QFTG) test. Those with a Mantoux test reading of ≥10 mm induration at 48–72 h and/or with a positive QFTG test, were given TB prophylaxis before initiating bDMARDs. They were followed and monitored for any features of tuberculosis flare. Results: A total of 730 patients (265 rheumatoid arthritis, 400 axial spondyloarthritis [axSpA], 34 psoriatic arthritis, and 31 others) were considered for bDMARDs. Two hundred and sixty-seven (36.6%) were positive for LTBI. They were treated either with isoniazid monotherapy for 6 months or with rifampicin + isoniazid for 4 months. bDMARDs were started 1 month after initiating chemoprophylaxis. Five (0.68%) patients developed active TB disease in the follow-up. In a total of 2930 “control” patients with the same diseases but never having taken bDMARDs, 18 (0.61%) developed active TB disease. The proportion of patients developing active TBI during the same period of follow-up did not differ between those who were and those who were not treated with bDMARDs. None of the study participants had “4S” symptoms. Conclusion: The strategy of clinical screening for active TBI with “4S complex,” standard chest radiograph, and an augmented Mantoux testing (10 TU purified protein derivative, [PPD]) simultaneously with QFTG test for the screening of LTBI, was successful in identifying active TBI in patients treated with bDMARDs.